Penerapan Metode Drill Pada Mata Pelajaran Matematika Pada Anak Berkebutuhan Khusus Gangguan Penglihatan (Tunanetra) di SLB Negeri 1 Pemalang - R. Neli Kismiati; Moh Muslih; Santika Lya Diah Pramesti; Umi Mahmudah (Prodi PGMI IAINU Kebeumen, 2021)
This study aims to reveal more deeply about how effective the implementation of the drill method in mathematics is for children with special needs (blind) at SLB Negeri 1 Pemalang. This research includes field research and the approach used is a qualitative approach. Data collection techniques are observation, interviews and documentation. The data sources are class IVA2 teachers and class VA teachers at SLB Negeri 1 Pemalang in mathematics, while the analysis used in this study is descriptive analysis. From the results of the application of the drill method in mathematics subjects, it produced satisfactory results, especially in the concept of multiplication in the form of rote memorization. The value of the results of the development of memorizing mathematical concepts is seen from the existing assessment rubrics.